Cognitive Disorders in Benign Childhood Epilepsy with Centrotemporal Spikes (BECTS) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
Intelligence and language functions were examined in 24 children (mean age 9 yrs; range 7-12 yrs) with BECTS and compared with a group of 16 controls matched for age and schooling, in a study at the Instituto Nazionale Neurologico, Milan, Italy.